Performing Discursive Inclusion in Platform-Native Journalism: A Critical Discourse Analysis of Religious Minority Representation on Indonesian YouTube News Media - Gustiara Gustiara; Siti Nurbaya (Journal of Religious Studies, 2025)
This study examines how religious minorities are represented and made intelligible within platform-native journalism, with particular attention to the discursive strategies employed by Indonesian digital news media on YouTube. The purpose of the study is to critically explore how intercultural meanings, inclusivity, and social legitimacy are constructed through audiovisual news content featuring minority religious groups, and how such representations operate within broader social and ideological contexts. Using a qualitative research design, the study applies Critical Discourse Analysis based on Teun A. van Dijk’s three-dimensional framework, encompassing textual structures, social cognition, and social context. The primary data consist of selected special-feature videos produced by Kumparan’s YouTube channel that focus on Sikh and Orthodox Christian communities in Indonesia, supported by secondary data from relevant literature and institutional documents. The findings reveal that platform-native journalism does not merely report on religious diversity but actively performs discursive inclusion through careful lexical choices, narrative framing, visual composition, and dialogic presentation. These strategies position minority religions as legitimate social actors while simultaneously aligning journalistic narratives with dominant norms of tolerance, harmony, and national pluralism. At the level of social cognition, the media organization demonstrates an awareness of its influential role in shaping public understanding of religious difference, while at the level of social context, the discourse reflects broader efforts to manage religious diversity within a multicultural society. The significance of this study lies in its contribution to religious and media studies by highlighting how digital journalism platforms function as sites where inclusion is not only articulated but enacted discursively. By foregrounding platform-native news practices, this research offers a nuanced understanding of religion, media power, and intercultural communication in contemporary society, making it relevant to international discussions on religion in the digital public sphere.